Community Development: A Case Study of Participation in the Lao-Swedish Forestry Programme - Somsoulivong, Vilayhak (2000)
This study was to assess community participation in the Lao Ngam Selected Field Area Project (LSFAP) and its influencing factors. It was conducted in 12 villages in the Lao Ngam district, the province of Saravanh, Laos, where the LSFAP was implemented. The general objectives of the study were to assess the level of participation and the factors influencing it during the third phase of the project (1992-1995). The specific objectives were to: (1) describe the operation of the LSFAP; (2) examIne the socio-demographic background of participants; (3) determine the level of participation existing in the villages in various activities; and (4) identify factors that influenced participation in the LSFAP. A total of 123 respondents involved in the 2 main activities: rice field ploughing and poultry raising in 12 villages were sampled using the proportionate sampling technique. Data for the study consisted of both qualitative and quantitative nature. The quantitative data was gathered by formal interviews while the qualitative data was collected using group discussion. Additional data were obtained by informal interviews and field observations. Structured questionnaires formed the main tool for the data collection. The quantitative data was analysed using descriptive frequency distribution to present and summarise the data. Pearson Correlation and Chi-square were used to determine the association between participation and all independent variables. The qualitative data was analysed by an inductive content technique. The study revealed that the level of participation of the project members in the LSFAP was at the medium level in all three stages: decision-making, implementation and benefit sharing. Education, politico-administrative support, project leadership, Community Development Board (VCDB) leadership, project member-project member (PM-PM) linkage and project member-project staff (PM-PS) linkage were found to have significant relationship with all the three stages of participation. However, in this study, only organisational membership had positive relationship in two stages of participation: decision-making and implementation.